Feasibility of catheter ablation renal denervation in "mild" resistant hypertension. Issue 4 (7th March 2017) - Chen, Shaojie; Kiuchi, Marcio Galindo; Acou, Willem‐Jan; Derndorfer, Michael; Wang, Jiazhi; Li, Ruotian; Kollias, Georgios; Martinek, Martin; Kiuchi, Tetsuaki; Pürerfellner, Helmut; Liu, Shaowen
Abstract: Renal denervation (RDN) has been proposed as a novel interventional antihypertensive technique. However, existing evidence was mainly from patients with severe resistant hypertension. The authors aimed to evaluate the efficacy of RDN in patients with resistant hypertension with mildly elevated blood pressure (BP). Studies of RDN in patients with mild resistant hypertension (systolic office BP 140–160 mm Hg despite treatment with three antihypertensive drugs including one diuretic, or mean systolic BP by 24‐hour ambulatory BP measurement [ABPM] 135–150 mm Hg) were included. Two observational and one randomized cohort were identified (109 patients in the RDN group and 36 patients in the control group). Overall, the mean age of patients was 62±10 years, and 69.7% were male. Before‐after comparison showed that RDN significantly reduced ABPM as compared with the baseline systolic ABPM, from 146.3±13 mm Hg at baseline to 134.6±14.7 mm Hg at 6‐month follow‐up and diastolic ABPM from 80.8±9.4 mm Hg at baseline to 75.5±9.8 mm Hg at 6‐month follow up (both P< .001). This significant effect was not observed in the control group. Between‐group comparison showed a greater change in ABPM in the RDN group as compared with that in the control group (change in systolic ABPM: −11.7±9.9 mm Hg in RDN vs −3.5±9.6 mm Hg in controls [ P< .001]; change in diastolic ABPM: −5.3±6.3 mm Hg in RDN vs −2.1±5.5 mm Hg in control [ P =.007]). RDN was also associated with a significantly decreased office systolic/diastolic BP and reduced number of antihypertensive medications. No severe adverse events were found during follow‐up. RDN seems feasible to treat patients with mild resistant hypertension.